Homens da Igreja : a participação de leigos católicos na política partidária em Aracaju - Carvalho, Joana Morato de (2013)
This work presents as study theme the set of relations between religion and politics. The objective is to apprehend the main insertion mechanisms used by layman Catholics who insert themselves in partisan politics mediated by their performances in the Catholic Church instances in Aracaju-SE. The empirical snippet was based on three layman Catholics notoriously recognized in Aracaju´s Catholic community. These agents engaged in Catholic´s Church religious movements, enabling the development of projects related to human rights, community issues and assistentialism. To understand the insertion mechanisms that were used for these layman Catholics to move from the religious sphere to the political sphere. This work proposes questions to understand their motivations to insert themselves in partisan politics through the examination of the socio-cultural living style present in their social trajectories which allowed access to the means of politicization and provisions for engaging in the Church instances.